2014
DOI: 10.5301/ijao.5000294
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis does not Adversely Affect Kidney Function Recovery after Congenital Heart Surgery

Abstract: Purpose Acute kidney injury (AKI) after cardiopulmonary bypass surgery to correct congenital heart disease is common. We prevent fluid overload and further cardiac compromise in oliguric infants with continuous peritoneal dialysis (CPD). The effect of CPD on kidney recovery is unknown, thus indications to discontinue CPD are unclear. We aimed to determine if CPD affects kidney recovery, measured by urine output and novel urinary AKI biomarker concentrations. Methods Twenty infants <90 days old with congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Some data suggest that early PD may decrease mortality and may not have an adverse effect on kidney recovery following AKI after congenital heart surgery. 24,25 This finding combined with that discussed above regarding preoperative small kidneys by renal ultrasound makes a reasonable argument for prophylactic placement of PD catheters in these select neonates.…”
Section: Discussionmentioning
confidence: 78%
“…Some data suggest that early PD may decrease mortality and may not have an adverse effect on kidney recovery following AKI after congenital heart surgery. 24,25 This finding combined with that discussed above regarding preoperative small kidneys by renal ultrasound makes a reasonable argument for prophylactic placement of PD catheters in these select neonates.…”
Section: Discussionmentioning
confidence: 78%
“…With regard to the timing for discontinuation of PD, Riley et al showed in a prospective randomized controlled study that PD continuation for a further 24 h was not effective in 20 infants under 90 days old. Although the group with PD continuation for a further 24 h had lower mean urine output, median levels of AKI biomarkers did not differ significantly between the groups [ 47 ]. Prophylactic peritoneal dialysis catheter placement and early initiation of PD may be effective, but more prospective randomized studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the lack of association between AKI and CKD development may in fact be because patients have not been followed long enough. 49,50,52,53 These studies did not specifically assess for the association between use of PD and long-term outcomes, but patients who received PD were included in the overall analysis.…”
Section: Methodsmentioning
confidence: 99%
“…51 Two studies have assessed the long-term outcomes of PD after congenital heart surgery. 52,53 Riley et al assessed for renal recovery in children who received PD after cardiac surgery and found no difference when measuring AKI biomarkers for the time course of recovery. In the study by Mel et al, survivors were followed between 3.5 to 10.5 years after their surgery, and long-term renal prognosis was reported as good, with no evidence of CKD at follow-up.…”
Section: Impact Of Pd On Long-term Outcomesmentioning
confidence: 99%